Analysis Of Factors Associated With Breast Milk Fluency In Breastfeeding Mothers In Postpartum Room Rsia Siti Khadijah - Retni, Ani; Lihu, Fahmi A.; Harismayanti, Harismayanti; Husain, Hardiyanti (Jurnal EduHealth, 2024)
Breast milk is recognized as the best nutrition for infants, providing essential energy and nutrients during the first six months of life, while also supporting immune function and cognitive development critical for a child's healthy growth. Despite its well-documented benefits, many mothers face challenges in initiating and maintaining exclusive breastfeeding, with one of the main barriers being insufficient milk production. In Indonesia, although efforts have been made to achieve 80% exclusive breastfeeding coverage, 2022 data shows that only 67.96% of infants under six months receive exclusive breastfeeding, a decline from the previous year. This study aims to identify the factors influencing the smooth flow of breast milk in Gorontalo, including family support, early initiation of breastfeeding (IMD), breastfeeding techniques, and maternal nutrition. The research employed a quantitative method with a cross-sectional design, conducted in the postpartum room of RSIA Siti Khadijah from July to August 2024, with a sample of 40 breastfeeding mothers selected through purposive sampling. Data were collected through questionnaires and analyzed using the chi-square test to examine the relationships between independent and dependent variables. The results indicated significant relationships between family support and smooth milk flow (p-value = 0.001 < 0.05), early initiation of breastfeeding (IMD) and smooth milk flow (p-value = 0.002 < 0.05), knowledge of breastfeeding techniques and smooth milk flow (p-value = 0.003 < 0.05), and maternal nutrition and smooth milk flow (p-value = 0.003 < 0.05). This study is expected to provide insights into the factors affecting breast milk flow and offer recommendations to improve exclusive breastfeeding coverage in Gorontalo, supporting the achievement of national targets, and providing guidance for designing more effective strategies tailored to the local context.